Rethinking Sino-Japanese competition: the diffusion of economic statecraft - Karl Yan; Jing Su (Asia Europe Journal, 2025)
The Belt and Road Initiative (BRI) has been one of the primary vehicles through which China exports its infrastructure and developmental standards. China's expanding ambitions to become an international standard-setter compelled a Japanese response. Shinzo Abe's government has initiated strategies such as the Partnership for Quality Infrastructure. This paper juxtaposes the Chinese and Japanese approaches to securing their position in the global governance of infrastructure finance, with a particular focus on the high-speed railway industry. It posits that economic statecraft has diffused from Japan to China and then back to Japan. In emulating Chinese economic statecraft, Japan has increased state involvement in infrastructure project exports and centralized authority within the Prime Minister's Office. The permeation of such statecraft and the apparent escalation of Sino-Japanese competition bear significant consequences for regional trade and developmental cooperation regimes. This heightened competition may initially afford South and Southeast Asian nations a broader choice of service and infrastructure providers. In the long run, if the competition solidifies, secondary states might find themselves compelled to integrate into either China's hub-and-spoke model or Japan's reinvigorated production networks. Moreover, such integration could render secondary states dependent on the technology and finance supplied by regional great powers. However, the eventual structure of the region will likely depend on how these two major powers navigate their rivalry. As South and Southeast Asian states and corporations become entwined in both states' geopolitical and geoeconomic networks, we cannot rule out the evolution of a latticework of intersecting relationships.
Keywords: 300; The belt and road initiative; Partnership for quality infrastructure; Sino-Japanese relations; The Chinese National Development and Reform Commission; Japanese Prime Minister's Office